1999
DOI: 10.1094/cchem.1999.76.3.389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Protein Content and Glutenin‐to‐Gliadin Ratio on the Functional Properties of Wheat Dough

Abstract: Gluten, starch, lipids, and water‐soluble material were separated from seven wheat samples with a range of protein contents and breadmaking quality. The isolated glutens were further partitioned into gliadin‐ and gluteninrich fractions using pH precipitation. Protein content and glutenin‐togliadin ratio were systematically altered by blending these fractions into the original flours in calculated amounts. Mixing properties, extension‐tester parameters, and baking performance of composite flours were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
114
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(145 citation statements)
references
References 9 publications
26
114
2
3
Order By: Relevance
“…The everyday practice of wheat quality evaluation and also numerous research works carrying out experiments by systematically altering the chemical composition of flour using supplementary flour components have already been determined certain effects of the protein content or the Glu/Gli ratio, etc. (Uthayakumaran et al 1999;Wrigley et al 2006). The relative amount of only certain supplementary components were altered in these special designed investigations, but the interference of many other components were not taken into consideration.…”
Section: Modelling Water Absorption With the Use Of Quantitative Protmentioning
confidence: 99%
See 1 more Smart Citation
“…The everyday practice of wheat quality evaluation and also numerous research works carrying out experiments by systematically altering the chemical composition of flour using supplementary flour components have already been determined certain effects of the protein content or the Glu/Gli ratio, etc. (Uthayakumaran et al 1999;Wrigley et al 2006). The relative amount of only certain supplementary components were altered in these special designed investigations, but the interference of many other components were not taken into consideration.…”
Section: Modelling Water Absorption With the Use Of Quantitative Protmentioning
confidence: 99%
“…One of the possibilities is the better utilization of the water binding potential of soluble protein-and pentosan-components. Experiments carried out with flour supplements of different protein classes, resulted the following observation: mixing requirements, dough strength and extensibility depended significantly on the glutenin to gliadin ratio, while the water absorption was not sensitive to that ratio (Uthayakumaran et al 1999), but was sensitive to the ratio of the gluten-to soluble-proteins (Tömösközi et al 2004). Supplementing wheat flour with soluble proteins of different origin and polarity showed that polarity/hydrophobicity as well as the charge distribution of albumins and globulins are the key features changing the amount of water needed for hydration (Tömösközi et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Glutenin subunits are linked by intermolecular disulphide bonds and form large glutenin polymers with molecular weights ranging from about 500,000 to more than 10 million (Shewry and Tatham, 1997;Wahlund et al, 1996). The proportion between glutenins and gliadins, as well as the allelic variations of both HMW-GS and LMW-GS in glutenins, have been shown to influence the technological properties of gluten, in particular breadmaking quality (Flaete and Uhlen, 2003;Gupta et al, 1994;Payne et al, 1979;1983;Uthayakumaran et al, 1999). Moreover, the proportion of the largest glutenin polymers, known as sodium dodecylsulphate-(SDS) unextractable polymeric proteins (UPP) or glutenin macropolymer (GMP), are associated with the strength and the elasticity of dough (Don et al, 2003;Gupta et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…7 The MWD is determined by the ratios of monomeric/polymeric proteins, HMW-GS/low-molecular-weight glutenin subunits (LMW-GS) and glutenin/gliadin. 5,[7][8][9][10][11][12] Indeed, the unusual properties of gluten proteins enable wheat flour to be transformed into dough with suitable properties for breadmaking.…”
Section: Introductionmentioning
confidence: 99%